2019
DOI: 10.1021/acsinfecdis.9b00275
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Tag Proteomic Analysis of in Vitro and in Vivo Models of Cutaneous Leishmaniasis Reveals Parasite-Specific and Nonspecific Modulation of Proteins in the Host

Abstract: Cutaneous leishmaniasis, the most common form of leishmaniasis, is endemic in several regions of the world, and if not treated properly, it can cause disfiguring scars on the skin. Leishmania spp. infection causes an inflammatory response in its host, and it modulates the host metabolism differently depending on the Leishmania species. Since Leishmania spp. has begun to develop resistance against current therapies, we believe efforts to identify new possibilities for treatment are critical for future control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
(94 reference statements)
1
10
0
Order By: Relevance
“…The same group [ 41 ] performed a similar experiment with skin biopsies and reported 17 DMP in infected mice. Further, they [ 42 ] adopted the labeled (tandem mass tag) proteomic approach and confirmed their earlier findings. Also, the study reported U6 snRNA-associated Sm-like protein and heat repeat-containing protein 3 to be precisely up-regulated in infection with L. major , while protein tweety homolog 3, phosphatidate cytidylyltransferase, and macrophage metalloelastase to be precisely up-regulated in infection with L. amazonensis .…”
Section: Differentially Modulated Proteins In the Host After supporting
confidence: 57%
See 3 more Smart Citations
“…The same group [ 41 ] performed a similar experiment with skin biopsies and reported 17 DMP in infected mice. Further, they [ 42 ] adopted the labeled (tandem mass tag) proteomic approach and confirmed their earlier findings. Also, the study reported U6 snRNA-associated Sm-like protein and heat repeat-containing protein 3 to be precisely up-regulated in infection with L. major , while protein tweety homolog 3, phosphatidate cytidylyltransferase, and macrophage metalloelastase to be precisely up-regulated in infection with L. amazonensis .…”
Section: Differentially Modulated Proteins In the Host After supporting
confidence: 57%
“…Despite the different experimental conditions and setup, heat-shock and Tryparedoxin related proteins were differentially regulated in 17 studies, indicating that those proteins are often modulated in the parasite. Moreover, several proteins were consistently identifiable and also to be similarly modulating in studies with similar experimental conditions [ 42 , 40 , 41 ]. Only three studies explored the host response (human subjects) during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, 100 μg of lytic protein per sample was reduced, alkylated, precipitated, resuspended and digested with trypsin before labelling. 35 Subsequently, 20 μL of TMT was added to each sample and mixed, and sodium deoxycholate clearing and peptide desalting were performed. 36 The pooled TMT-labelled peptides were then separated and analysed using a reversed-phase high-performance liquid chromatography and a nano-UPLC (EASY-nLC 1200) coupled to a Q-Exactive mass spectrometer (Thermo Finnigan) as previously described.…”
Section: Tandem Mass Tag™ Labelling Quantitative Proteomicsmentioning
confidence: 99%